A Contextualized Layered Risk Management Framework for Indian Medical Laboratories - Yogesh R Pawade; Anita S Chalak; Hemant S Dahake (Indian Journal of Medical Biochemistry)
Introduction: Medical laboratories are indispensable to modern health care; yet their operations inherently involve risks that can undermine quality and safety if not effectively managed. While established risk management frameworks exist, their direct applicability to the diverse and resource-variable landscape of Indian laboratories is questionable. A significant gap exists in comprehensive studies dedicated to developing a context-specific risk management framework tailored to the unique challenges of Indian laboratories, encompassing small private setups to large public health institutions. This study introduces a novel, layered approach to risk management designed to address this gap. Objective: This study aimed to develop a customized, layered risk management framework meticulously tailored to the specific characteristics and diverse requirements of medical laboratories operating across India. The framework is designed to be adaptable to different contexts and levels of health care within the Indian system. Materials and methods: The interventional study was conducted within the Central Clinical Biochemistry Laboratory under Department of Biochemistry at Seth Gordhandas Sunderdas Medical College and King Edward Memorial Hospital, Mumbai, from January to June 2024. A mixed-methods approach was employed, focusing on comprehensive risk understanding, development of a context-sensitive, layered solution, and evaluation of its potential effectiveness. This included a thorough literature review of international quality standards and best practices pertaining to risk management in laboratories. Building upon this review, a customized, layered risk management framework (layers 1, 2, and 3) is proposed. This framework utilizes a tiered approach to risk analysis, beginning with broad identification and progressing to detailed evaluation. It incorporates Failure Mode and Effects Analysis to analyze potential failure modes across various laboratory processes. Risk prioritization is achieved through a customized probability, severity, and detectability scale, specifically adapted to reflect the realities and challenges of the Indian laboratory context. The initial risk screening layer utilizes a Risk Priority Number (RPN) calculated from these scales, guiding the subsequent layers of more detailed analysis for higher-priority risks. Results: This study successfully demonstrated the conceptual implementation of a tailored, layered risk management plan within a real-world laboratory setting. It effectively illustrated a customized, layered risk analysis approach, employing tiered likelihood, severity, and detection scales within a risk matrix framework. The findings underscore the importance of the RPN in guiding prioritization decisions within a layered system. The study highlights the value of implementing progressively detailed control measures, informed by the risk layer, along with the necessity for regular monitoring and re-evaluation at each layer to ensure ongoing effectiveness and adaptability of the risk management framework. Conclusion: The proposed layered risk management framework, customized to the specific and varied needs of Indian laboratories, emphasizes a tiered approach to risk mitigation. At its foundation, it prioritizes essential and readily implementable controls. For higher-priority risks identified within these initial layers and progressing to deeper layers, it advocates for more resource-intensive but potentially more impactful strategies, like digital solutions and collaborative initiatives. Training remains a cornerstone across all layers. The layered framework promotes continuous improvement by facilitating regular reviews and adjustments within each layer. By tailoring control measures in a layered fashion, building capacity through targeted training, and fostering collaborative partnerships, medical laboratories in India can more effectively mitigate risks, enhance the quality of their services, and ultimately contribute to improved patient safety within India's complex and diverse healthcare landscape.